(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce and investigate a family of analytic functions, denoted by F(Π, α, β, λ, δ, μ), defined by means of Horadam polynomials. For functions in this family, we derive the estimations for the initial Taylor-Maclaurin coefficients |a_2| and |a_3|. Moreover, we obtain the classical Fekete-Szegö inequality of functions belonging to this family.